Pengaruh Kompetensi, Penempatan dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Samsat Kab. Bima - Fadilah, Nur; Badar, Muhammad; Jaenab, Jaenab (Jurnal Ekonomi, Bisnis dan Manajemen, 2025)
This study aims to examine the influence of competence, job placement, and work discipline on employee performance at the Samsat Office of Bima Regency. The research applies a quantitative approach using a survey method. Data were collected through questionnaires distributed to 30 civil servants selected using purposive sampling. The data analysis techniques include validity and reliability tests, multiple linear regression, t-test, and F-test. The results show that competence, placement, and work discipline each have a positive and significant influence on employee performance, both partially and simultaneously. The coefficient of determination indicates that 45.2% of the variance in performance is explained by the three variables. These findings suggest that improving employee competence through training, placing staff according to their skills, and consistently enforcing work discipline can enhance employee effectiveness and productivity. The study has important implications for human resource management in public institutions, particularly in improving service quality through better employee performance.